2005
DOI: 10.1073/pnas.0502365102
|View full text |Cite
|
Sign up to set email alerts
|

Comparative physical mapping links conservation of microsynteny to chromosome structure and recombination in grasses

Abstract: Nearly finished sequences for model organisms provide a foundation from which to explore genomic diversity among other taxonomic groups. We explore genome-wide microsynteny patterns between the rice sequence and two sorghum physical maps that integrate genetic markers, bacterial artificial chromosome (BAC) fingerprints, and BAC hybridization data. The sorghum maps largely tile a genomic component containing 41% of BACs but 80% of single-copy genes that shows conserved microsynteny with rice and partially tile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
116
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(128 citation statements)
references
References 44 publications
12
116
0
Order By: Relevance
“…BAC clones corresponding to RT-enriched genes from S. propinquum and S. bicolor By hybridization of gene-specific overgos, we have identified the BAC clones and number of contigs (genetic loci) at which family members of each gene are represented in the physical maps of both S. bicolor and S. propinquum (Bowers et al, 2005). A total of 24 genes of S. proqinquum were anchored to only one locus, whereas 17 genes occurred at 2-10 loci and 9 genes at more than 10 loci.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…BAC clones corresponding to RT-enriched genes from S. propinquum and S. bicolor By hybridization of gene-specific overgos, we have identified the BAC clones and number of contigs (genetic loci) at which family members of each gene are represented in the physical maps of both S. bicolor and S. propinquum (Bowers et al, 2005). A total of 24 genes of S. proqinquum were anchored to only one locus, whereas 17 genes occurred at 2-10 loci and 9 genes at more than 10 loci.…”
Section: Resultsmentioning
confidence: 99%
“…Six clones that were enriched in RT relative to RMI were also RT-enriched relative to AG, resulting in a total of 54 clones that were further analyzed herein. Overgo probes were designed from the sequences of each of 54 RT-enriched genes by BLAST comparison against other plant species to identify the most-conserved 40 bp sequences as described (Bowers et al, 2005). For gene sequences with no matches to any other plant species, arbitrary 40 bp sequences were used as overgo probes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammals, gene order conservation has been associated with the regulation of gene expression (Semon and Duret, 2006;Gierman et al, 2007), replication, and chromatin structure (Huvet et al, 2007). Nonrandom patterns of gene expression are found among proximally located rice (Ma et al, 2005) and Arabidopsis (Ren et al, 2007) genes. While a comparative study to date found no microsynteny between the two species in these domains (Ren et al, 2007), inferences about monocot-dicot synteny are much more complicated than was realized before the availability of whole-genome sequences (Paterson et al, 1996), due largely to multiple paleopolyploidies and associated gene losses.…”
Section: Distinguishing Features Of the Cerealsmentioning
confidence: 99%
“…While the Oryza-Sorghum-Brachypodium group is still viewed as having evolved relatively slowly, grasses that have been through recent genome duplications have undergone substantial fractionation of ancestral gene orders across multiple chromosomes. For example, there is greater similarity of gene order between the genomes of sorghum and rice, diverged by 40 to 50 million years Bowers et al, 2005), than between the genomes of sorghum and maize, diverged by 10 to 15 million years (Bowers et al, 2003). As yet unknown factors other than polyploidy also influence grass genome stability.…”
Section: Distinguishing Features Of the Cerealsmentioning
confidence: 99%